Winning the story wars : why those who tell - and live - the best stories will rule the future - Sachs, Jonah (Boston, Massachusetts Harvard Business Review, 2012)
Argues that only those brands that tell values-driven stories through the right channels will revolutionize marketing. The author systematically breaks down how communicators can go beyond the sell by creating stories that inspire people not just to listen, but to proselytize
Keywords: Medios de comunicación social; Consumidores -- Comportamiento; Marketing -- Aspectos sociales